Hipotensi Berhubungan dengan Kejadian Post Operative Nausea and Vomiting pada Pasien Pasca Anestesi General dan Anestesi Sub Arahnoid Block - Sugianto, Sugianto; Bakar, Abu (Journal of Telenursing (JOTING), 2023)
This study aims to identify decreased blood pressure and postoperative nausea and vomiting (PONV) in patients post general anesthesia and sub-arachnoid block (SAB) anesthesia. The research method used is descriptive statistics. The study showed a relationship between hypotension and the incidence of PONV in patients receiving general anesthesia, as indicated by the results of the contingency coefficient test, which had a significant value of 0.018. The study's results also showed a relationship between hypotension and the incidence of PONV in patients receiving SAB anesthesia, as indicated by the results of the contingency coefficient test, which had a significant value of 0.027. In conclusion, there is a relationship between a decrease in blood pressure and the incidence of PONV in patients who received general anesthesia and SAB anesthesia at Aisyiyah Bojonegoro Hospital. Keywords: General Anesthesia, Hypotension, PONV, Sub Arachnoid Block (SAB)